Disturbance indicator values for European plants. Issue 1 (19th October 2022) - Midolo, Gabriele; Herben, Tomáš; Axmanová, Irena; Marcenò, Corrado; Pätsch, Ricarda; Bruelheide, Helge; Karger, Dirk Nikolaus; Aćić, Svetlana; Bergamini, Ariel; Bergmeier, Erwin; Biurrun, Idoia; Bonari, Gianmaria; et al.
Abstract: Motivation: Indicator values are numerical values used to characterize the ecological niches of species and to estimate their occurrence along gradients. Indicator values on climatic and edaphic niches of plant species have received considerable attention in ecological research, whereas data on the optimal positioning of species along disturbance gradients are less developed. Here, we present a new data set of disturbance indicator values identifying optima along gradients of natural and anthropogenic disturbance for 6382 vascular plant species based on the analysis of 736, 366 European vegetation plots and using expert‐based characterization of disturbance regimes in 236 habitat types. The indicator values presented here are crucial for integrating disturbance niche optima into large‐scale vegetation analyses and macroecological studies. Main types of variables contained: We set up five main continuous indicator values for European vascular plants: disturbance severity, disturbance frequency, mowing frequency, grazing pressure and soil disturbance. The first two indicators are provided separately for the whole community and for the herb layer. We calculated the values as the average of expert‐based estimates of disturbance values in all habitat types where a species occurs, weighted by the number of plots in which the species occurs within a given habitat type. Spatial location and grain: Europe. Vegetation plots ranging in size from 1 to 1000 m 2 . Time period and grain: Vegetation plots mostly sampled between 1956 and 2013 (= 5th and 95th quantiles of the sampling year, respectively). Major taxa and level of measurement: Species‐level indicator values for vascular plants. Software format: csv file.